Reinwardtia indica: phytochemical screening and evaluation of wound healing activity of the extracts in experimental model rats - Gurung, Roshani; Koirala, Niranjan; Gurung, Paru; Tamang, Bishnu Maya; Chettri, Sarita; Basnet, Bibek; Pandey, Trishna; Nassan, Mohamed A.; Alqarni, Mohammed; Batiha, Gaber El-Saber; Adhikari, Sundar (Cellular and Molecular Biology, 2021)
Reinwardtia indica is traditionally used for wound healing. The main aim of this study was to evaluate the wound healing activity of leaves extracts of R. indica using the excision wound model in rats. The leaves of R. indica were collected from Gondrang, Chitwan, Nepal. Leaves were shade dried, extracted by double maceration and subjected to phytochemical screening. Then, the fusion method was used for the formulation of ointment and evaluated. Rats (n=24) were divided into four groups with 6 in each. Excision wound model was used, 2 cm diameter (314 mm2), 2 mm depth wound was created. The treatment was given daily topically to all groups and the % mean wound contraction rate was calculated on days 4, 8, 12 and 16. The result was analyzed statistically using Graph pad prism version 5. Phytochemical test revealed the presence of alkaloid, flavonoid, tannin, phenol, terpenoid, carbohydrate, etc. All the evaluation parameters showed satisfactory results. The extract of R. indica ointment (2% w/w and 5% w/w) increased the wound contraction rate day by day. The % means wound contraction rate, on day 12, (80% and 88%), and on day 16, (97% and 100%) and statistically significant difference was at p<0.0001. The R. indica extract ointment showed an increased wound contraction rate. So, in further R. indica could be used for commercial production of wound healing ointment.